THE IMPROVEMENT OF STUDENTS' CONCEPTUAL COMPREHENSION ON HEAT TRANSFER THROUGH THE USE OF FEMLAB-BASED INTERACTIVE MULTIMEDIA - hamidah, Ida; Mulyanti, Budi, Sulaeman; Wibisono, Yudi (Journal of Technical Education and Training, 2022)
The purpose of this research is to study the effect of using a Finite Element Method Laboratory (FEMLAB)- based multimedia on students’ conceptual comprehension on heat transfer material. The research used a preexperimental design method and the intervention includes interactive media which contains conceptual information on conduction, convection, and radiation. The participants were students in the 3rd semester from the mechanical engineering department in the Indonesian University of Education. Through series of data analysis, high category of N-gain score (0.72) is obtained with the highest comprehension score being in the concept of radiation ( = 0.86) compared to other two concepts; convection and conduction. Moreover, under the discussion of comprehension skills, a high score is also obtained at the level of 0.86 which belongs to the translation skills compared to the interpretation and extrapolation skill. Having such a result, it can be seen that score of conceptual comprehension on heat transfer subject is in the high-g level, so it can be concluded that the use of FEMLAB-based multimedia has effectively improves the students’ conceptual comprehension. Beside that, the students give positive response toward the use of FEMLAB-based multimedia which can create a more fun learning experience in heat transfer material and can facilitate the students to independently master the related concepts.